2020
DOI: 10.1007/s10534-020-00274-w
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione and the intracellular labile heme pool

Abstract: One candidate for the cytosolic labile iron pool is iron(II)glutathione. There is also a widely held opinion that an equivalent cytosolic labile heme pool exists and that this pool is important for the intracellular transfer of heme. Here we describe a study designed to characterise conjugates that form between heme and glutathione. In contrast to hydrated iron(II), heme reacts with glutathione, under aerobic conditions, to form the stable hematin–glutathione complex, which contains iron(III). Thus, glutathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…In the current report, we exploited HO-2 selectivity for ferric heme over ferrous heme (86) and perturbations to its expression by silencing or over-expression to infer that LH is largely oxidized (Figure 6). These findings suggest that the glutathione redox buffer does not equilibrate with LH to keep it reduced and supports prior studies that found glutathione binds oxidized heme too weakly (KD III = 20 M) to represent a physiologically relevant buffering factor (90). LH being oxidized is consistent with the observation that DNA and RNA guanine quadruplexes, which have nM affinities for ferric heme, also appear to bind and regulate heme availability in human cell lines (67,71).…”
Section: Discussionsupporting
confidence: 89%
“…In the current report, we exploited HO-2 selectivity for ferric heme over ferrous heme (86) and perturbations to its expression by silencing or over-expression to infer that LH is largely oxidized (Figure 6). These findings suggest that the glutathione redox buffer does not equilibrate with LH to keep it reduced and supports prior studies that found glutathione binds oxidized heme too weakly (KD III = 20 M) to represent a physiologically relevant buffering factor (90). LH being oxidized is consistent with the observation that DNA and RNA guanine quadruplexes, which have nM affinities for ferric heme, also appear to bind and regulate heme availability in human cell lines (67,71).…”
Section: Discussionsupporting
confidence: 89%
“…In recent years the term “labile heme” has appeared. ,,,, The use of this term allows a distinction to be made between the proportion of the total heme content that is available for mobilization, and the proportion that is unavailable (or, more precisely, inert for exchange) because it is bound with a high affinity, and therefore irreversibly, to proteins. Ideas on what the concepts of labile heme actually means mimic the early ideas on free heme. , Labile heme is envisaged as being continuously engaged in transient binding to intracellular proteins that exist to actively buffer heme concentrations in the cell.…”
Section: Terminologymentioning
confidence: 99%
“…However, while the machinery for heme synthesis and degradation is well known, a decades-old question has been to establish precisely how heme is transported between its place of synthesis and subsequently made available to other regions of the cell where heme is in demand. Recent published work has hypothesized that membrane structures ( 3 ) and membrane contacts ( 4 ) are involved in the heme trafficking mechanism. Nevertheless, the scarcity of information in this area stands in stark contrast to the extensive efforts that have been directed toward understanding the structures and reactivities of many different heme proteins (e.g., refs.…”
mentioning
confidence: 99%